The Division Of Husband–Wife Roles In Pottery-Crafting Families: A Mubādalah Perspective On Family Relations In Sitiwinangun, Cirebon - Fitri Nurajizah; Edy Setyawan; Asep Saepullah (Universitas Ibn Khaldun Bogor, 2026)
The division of roles between husbands and wives is an important issue in contemporary family life, particularly in households whose economic activities are carried out jointly. In pottery-crafting families, productive activities are often closely connected with domestic responsibilities, creating diverse patterns of husband–wife relations. This study examines the division of roles between husbands and wives in pottery-crafting families in Sitiwinangun Village, Jamblang District, Cirebon Regency, from the perspective of Mubādalah. This study employs a qualitative field-research approach. Data were collected through observation, in-depth interviews, and documentation involving four pottery-crafting families as research subjects. The analysis uses Scanzoni’s theory of family relations to identify patterns of husband–wife relationships and the Mubādalah approach to assess reciprocity, equality, mutuality, deliberation, and shared responsibility within family life. The findings reveal four patterns of husband–wife relations. The Marini–Dija family reflects a senior–junior partner pattern, the Kadmiya–Carini family reflects an owner–property pattern, the Jaji–Maya family reflects a head–complement pattern, and the Rasiti–Ukata family reflects an equal-partner pattern. The findings further indicate that women’s participation in economic activities does not automatically produce equality in family relations. Equality is more strongly influenced by the distribution of domestic and productive responsibilities, economic decision-making, and the extent to which important family matters are determined through deliberation. From the Mubādalah perspective, the equal-partner pattern most clearly reflects the principles of mutuality and reciprocity because productive, domestic, and decision-making responsibilities are negotiated according to the capacities and circumstances of both spouses. The study concludes that strengthening reciprocal husband–wife relations requires not only recognition of women’s economic contributions but also shared responsibility and consistent deliberation in family decision-making.